Warsaw Ghetto police : the Jewish Order Service during the Nazi occupation - Person, Katarzyna; Nowak-Soliński, Zygmunt (Ithaca [New York] : Cornell University Press, 2021)
"Focuses on the history of the Jewish Order Service (known as the Jewish Police) in the Warsaw Ghetto, 1940-1943 and its perception among ghetto inhabitants"--
Establishment of the Jewish Order Service -- Organization and the objectives of the Service -- Violence and corruption in the exercise of daily duties -- Police in the eyes of the ghetto population: interpretation of violence -- Police officers' voices -- Response to violence: regulation of the activity of the Jewish Order Service -- Spring -- Umschlagplatz -- After resettlement -- The courts.
"Published in association with the United States Holocaust Memorial Museum."
Includes bibliographical references and indexes.
Translated from the Polish.
Description based on online resource; title from digital title page (viewed on March 31, 2021).
JSTOR
Keywords: Jüdischer Ordnungsdienst -- History; Holocaust, Jewish (1939-1945) -- Poland -- Warsaw; Jews -- Poland -- Warsaw -- History -- 20th century; Getto warszawskie (Warsaw, Poland); Holocauste, 1939-1945 -- Pologne -- Varsovie; Juifs -- Pologne -- Varsovie -- Histoire -- 20e siècle.; HISTORY / Jewish; Jews; Poland -- Warsaw; Poland -- Warsaw -- Getto warszawskie; 1900-1999; Jewish Police during the Holocaust, Jewish Order Service of the Warsaw Ghetto, Umschlagplatz, death camp of Treblinka; History